2010
DOI: 10.1016/j.dental.2010.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Five-year survival of 3-unit fiber-reinforced composite fixed partial dentures in the posterior area

Abstract: A success rate of 71% and a survival rate of 78% after 5 years was found. Survival rates of inlay, hybrid and surface retained FPDs did not significantly differ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 16 publications
(18 reference statements)
3
48
0
7
Order By: Relevance
“…The results of this study exhibited a mean fracture strength higher that 1,700 N. Results that could position these types of prostheses as suitable and strong enough to be used in clinical applications. That suitability has been previously noted 7,[32][33][34] , where successful applications of FRC restorations in clinical dentistry was reported. In addition, various studies have shown improved aspects of FRCs such as flexural and fatigue properties, framework design, and load-bearing capacities 14,35) .…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…The results of this study exhibited a mean fracture strength higher that 1,700 N. Results that could position these types of prostheses as suitable and strong enough to be used in clinical applications. That suitability has been previously noted 7,[32][33][34] , where successful applications of FRC restorations in clinical dentistry was reported. In addition, various studies have shown improved aspects of FRCs such as flexural and fatigue properties, framework design, and load-bearing capacities 14,35) .…”
Section: Resultssupporting
confidence: 61%
“…In addition, various studies have shown improved aspects of FRCs such as flexural and fatigue properties, framework design, and load-bearing capacities 14,35) . Clinical studies have reported veneering composite fractures as the most common mode of failure observed 32) . This failure type is attributed to an insufficient support at the pontic area that could be solved by using a bundle of fibers oriented perpendicularly towards longitudinal fibers 33) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, there is limited information on the longevity and clinical behavior of FRC FDPs, available clinical studies showed that FRC FDPs are able to function acceptable with reported five year-survival rates ranging between 73% (Göhring and Roos, 2005) and 78% (van Heumen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…When single studies were evaluated, similar failure types were observed in a multicenter study at 5 years with success rate of 71.2% and survival rate of 77.5% where the restoration types showed heterogeneity of inlay, hybrid and surface-retained posterior FPDs, where the latter showed more debonding. 31 As for anterior surface-retained FRC FDPs, again in a multicenter study where more operators were involved, at 5 years, The rapid development and relatively short clinical history of the current resin-bonded FRC FDP technique have given rise to concerns on the through evaluation of this procedure. However, situations where implant prognosis is questionable, young patients due to biological price of the dental tissues or patients with economical limitations could be offered such an alternative which was also reported to increase oral health related quality of life.…”
mentioning
confidence: 99%